Pengaruh Angka Partisipasi Sekolah (APS) Dan Tingkat Partisipasi Angkatan Kerja (TPAK) Terhadap Indeks Pembangunan Manusia (IPM) di Indonesia - Nastiti, Anggi Wida; Nailufar, Fanny (LPPM UNIMAL, 2023)
This study aims to determine the effect of the School Participation Rate (SPR) and the Labor Force Participation Rate (LFPR)) on the Human Development Index (HDI in Indonesia. This study uses secondary data sourced from the Indonesian Central Bureau of Statistics (BPS) for the 2012-2021 period. Data were analyzed using the Multiple Linear Regression analysis method. The results of the research partially show that the variable School Participation Rate (SPR) has a positive and significant effect on the Human Development Index (HDI) and the Labor Force Participation Rate variable (LFPR) has no effect and is not significant on the Human Development Index (HDI) in Indonesia. The results of the study simultaneously with the School Participation Rate (SPR) and Labor Force Participation Rate (LFPR) variables have a positive and significant effect on the Human Development Index (HDI) variable.